Mortal Remains : Death in Early America - Burstein, Andrew; Isenberg, Nancy (Book collections on Project MUSE., 2003)
"These 12 short, highly focused essays analyze how experiences with death and the imagery associated with it influenced US culture before 1860"--Choice